Relative identity by Peter Geach and Gilles Deleuze’s concept of difference - Kociołek, Kamil; Sonek, Robert (Hybris, 2020)
The area in which the philosophy attributed to the "analytic" tradition turns out to consider similar problems as the "continental" thinkers still seems to be too little explored. The aim of the work is to indicate such similarities between the Peter Geach’s concept of relative identity and the Gilles Deleuze’s concept of difference. According to Geach, identity is mediated in concepts. We think about the identity of "a" and "b" only in the sentence "a is the same X as b". The consequences of this observation are twofold: on the one hand, it shows the degree of our entanglement in conceptual grids; on the other, it shows a being as a dynamic, relational structure. In this aspects, this perspective agrees with Deleuze's proposal. A being is an ambiguous intersection of dynamic relations expressed in the sentence "a is different from b", whereas the identity is an effect of totalitarian thought movement which reduces differences by imposing static conceptual categories on their dynamic system. We are going to present the ontological view on identity question which synthesizes two mentioned conceptions and include a polemical characterization of difficulties implied by discussed perspective and their consequences for practical functioning in the world.